HUBUNGAN PENGETAHUAN TENTANG SWAMEDIKASI DENGAN POLA PENGGUNAAN OBAT PADA MASYARAKAT PADANG BINTUNGAN DHARMASRAYA - Ita Dwiaini (Nusantara Hasana Journal, 2022)
Self-medication is one of the effort by someone to maintaining their health using the medicine, based on self initiative or without medical consultation. Self- medication has some benefits and some risks. This research purpose to identified the relation of the knowledge about self-medication with the pattern of drug use in Padang Bintungan Dharnasraya Community. This research was designed analytic cross sectional observational. The technique in collected sample was using method of non random sampling, which was the respondents were above 18 years old, chosen by accidental sampling. The data collected using the questioners that the validity and the reliability has been tested. Characteristics the respondents analyze in statistics descriptive in the form of percentages and present by diagram and tables, while analytical data analyze with Rank Spearman and Correlation Coefficient Theta. There were 56 respondents participated in this research. Around 56% respondents have great knowledge. There was no significant correlation and very weak or very low correlation between the knowledge and the pattern of drugs that been consumed, the place of buying the drugs, distance, types of the drugs, price of the drugs and the sources of informations